Deadpool team-up. Blood of the dragon - Liefeld, Rob (Marvel Worldwide, Inc., 2025)
When you need a hired hand, Deadpool is your man! But when Wade Wilson needs assistance, he's got friends (and frenemies) from across the Marvel Universe he can count on! And the return of a lost Marvel Comics character will necessitate the ultimate team-up mission - bringing Deadpool together with Major X, Crystar, Ghost-Spider, Wolverine and the Hulk! But who is Ral Dorn, and how does the Dragon Lord factor into this mission?!